Интеллектуализация труда - основа развития современной экономики - Булеев, И.П.; Булеев, Е.И.; Брюховецкий, Я.С. (Стратегія і механізми регулювання промислового розвитку, 2016)
Исследованы проблемы интеллектуализации труда в условиях IV технологической революции, становления V-VI технологических укладов в постсоциалистических странах и Украине. Показан приоритет развития интеллектуального труда. Доказана необходимость опережающей подготовки работников интеллектуального труда. Определены основные направления роста интеллектуализации труда в Украине в целом, в промышленности и на предприятиях в частности. Досліджено проблеми інтелектуалізації праці в умовах IV технологічної революції, становлення V-VI технологічних укладів у постсоціалістичних країнах та Україні. Обґрунтовано пріоритет розвитку інтелектуальної праці. Доведено необхідність випереджаючої підготовки працівників інтелектуальної праці. Визначено основні напрями зростання інтелектуалізації праці в Україні загалом, у промисловості та на підприємствах зокрема. The problems of correlation of physical and mental labor at different stages of development of human society are considered. The general tendency is the advancing development of mental labor relative to the physical. Under the conditions of the capitalist mode of production, mental labor becomes predominant, reaching, in certain conditions and industries, up to 50-70% of commodity output, GDP. Mental labor becomes the basis of intellectual capital. In the process of research, an algorithm has been developed for the formation of a system of intellectualization of labor from family, preschool, school and higher educa-tion to the periodic renewal of human values and professional knowledge throughout the work of a person. The features of the development and functioning of intellectual labor in the countries of classical capitalism, in the post-Soviet and post-socialist countries, in Ukraine are shown. It is proved that the professional and scientific components of the intellectual training of modern workers should outstrip the level of technical and technological development of production. The main directions of development and correlation of branch, academic and high school science in Ukraine are determined. Proposals have been made to improve the financing of science and education in Ukraine.